Finding and following God's will - Kise, Jane A. G. (Minneapolis, Minn. : BethanyHouse, 2005)
"How, when, and why does God talk to people today? In tackling these questions, this book helps readers discern God's will for their lives"--Provided by the publisher.
Keywords: Discernment (Christian theology); God (Christianity) -- Will